Evaluation of a faecal calprotectin care pathway for use in primary care. Issue 5 (22nd February 2016) - Turvill, James; O'Connell, Shaun; Brooks, Abigail; Bradley-Wood, Karen; Laing, James; Thiagarajan, Swaminathan; Hammond, David; Turnock, Daniel; Jones, Alison; Sood, Ruchit; Ford, Alex
Abstract : Background: National Institute for Health and Care Excellence have recommended faecal calprotectin (FC) testing as an option in adults with lower gastrointestinal symptoms for whom specialist investigations are being considered, if cancer is not suspected and it is used to support a diagnosis of inflammatory bowel disease (IBD) or irritable bowel syndrome. York Hospital and Vale of York Clinical Commissioning Group have developed an evidence-based care pathway to support this recommendation for use in primary care. It incorporates a higher FC cut-off value, a 'traffic light' system for risk and a clinical management pathway. Objectives: To evaluate this care pathway. Methods: The care pathway was introduced into five primary care practices for a period of six months and the clinical outcomes of patients were evaluated. Negative and positive predictive values (NPV and PPV) were calculated. GP feedback of the care pathway was obtained by means of a web-based survey. Comparator gastroenterology activity in a neighbouring trust was obtained. Results: The care pathway for FC in primary care had a 97% NPV and a 40% PPV. This was better than GP clinical judgement alone and doubled the PPV compared with the standard FC cut-off (<50 mcg/g), without affecting the NPV. In total, 89% of patients with IBD had an FC>250 mcg/g and were diagnosed by 'straight to test' colonoscopy within three weeks. The care pathway was considered helpful by GPs and delivered a higher diagnostic yield after secondary care referral (21%) than the conventional comparator pathway (5%). Conclusions: A care pathway for the use of FC that incorporates a higher cut-off value, a 'traffic light' system for risk and supports clinical decision making can be achieved safely and effectively. It maintains the balance between a high NPV and an acceptable PPV. A modified care pathway for the use of FC in primary care is proposed.